UTAR landscaping with Virtual Reality (VR) - Tang, Shun Xin (2023)
This project is to build VR model of UTAR landscape for academic purpose. The UTAR Landscaping with VR provide any people to have chances to view and familiar with the UTAR Kampar campus environment including the overview landscape of UTAR Kampar campus, the special landmark of the campus. User can roam freely inside the VR landscape of campus. Minimap function will also be included in this project. Minimap that can track users’ location and allow user to teleport to nearby of the specific places in the project. This project is inspired due to Movement Control Order (MCO) that causes most people to be restricted in their house. All the students had to continue their study in online teaching and learning mode (OTL). These causes most of the students especially the new intake students do not have any opportunity to know more about campus and its environment. Besides that, due to MCO, physical group events and activities such as convocation were not allowed thus the students that graduate during the period does not have chance to went for their convocation physically and may left some regrets. Besides that, the software used to develop UTAR landscape is using Unity 3D. Most of the landscape model can be found and used in unity but there is some special landmark there need other software such as 3Ds Max to build. The script that need in the project will coded using C# language with the editor Microsoft Visual Studio.